1987
DOI: 10.1111/j.1432-1033.1987.tb10535.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding mode of nucleosome‐assembly protein (AP‐I) and histones

Abstract: Studies were made on the binding mode of the nucleosome-assembly protein AP-I with histones H2A + H2B and/or H3 + H4. Histones H2A + H2B bound with AP-I to form a 7-S complex which contained twice as much AP-I (by weight) as histones. Histone H3 + H4 formed an 8-S complex with AP-I. The 7-S and 8-S complexes did not form a new complex when mixed, but significant amounts of two histone pairs were assembled into a 12-S complex on mixing the (H2A + H2B)-AP-I complex (7-S) with free H3 + H4. In contrast, when the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
4
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 25 publications
4
75
4
1
Order By: Relevance
“…8), which forms a short a-helix and contacts the Cterminal tail of histone H4 in the nucleosome. Interestingly, NAP-1, a close homologue of TAF-I, which also appears to function as a chaperone and facilitates deposition of histones onto DNA (Ishimi & Kikuchi, 1991;Ishimi et al, 1987;McQuibban et al, 1998), has been found to be associated with histone H2A in co-immunoprecipitation analysis (Chang et al, 1997). Analysis of interactions with deletion mutants of VP22 should help define whether this region is important in the TAF-I interaction.…”
Section: Discussionmentioning
confidence: 99%
“…8), which forms a short a-helix and contacts the Cterminal tail of histone H4 in the nucleosome. Interestingly, NAP-1, a close homologue of TAF-I, which also appears to function as a chaperone and facilitates deposition of histones onto DNA (Ishimi & Kikuchi, 1991;Ishimi et al, 1987;McQuibban et al, 1998), has been found to be associated with histone H2A in co-immunoprecipitation analysis (Chang et al, 1997). Analysis of interactions with deletion mutants of VP22 should help define whether this region is important in the TAF-I interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Nucleosome assembly protein (NAP-I), which contains three negatively charged regions, is found in various eukaryotic cells and has been shown to interact with cellular histones and to facilitate nucleosome formation (Fujii-Nakata et al 1992;Ishimi et al 1987). Here we examined whether NAP-I also has similar stimulatory activity in the transcription assay as in the replication assay (Fig.…”
Section: Substitution For Taf-i By Nap-imentioning
confidence: 99%
“…NAP-I facilitates the formation of nucleosomes by interacting with cellular histones and transferring them to DNA (Ishimi et al 1987;Ishimi & Kikuchi 1991;Fujii-Nakata et al 1992). Since NAP-I can substitute for TAF-I in the replication and transcription ( Fig.…”
Section: Taf-i Has the Nap-i Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18]20,21 In humans, the NAP family members include NAP1, NAP1-like protein (NAP1L), SE translocation (SET), testis-specific protein, Y-encoded (TSPY), and testis-specific protein, Y-encoded like (TSPYL). 17,20,[22][23][24][25][26] It is known that proteins in the NAP family participate in chromatin structure and diverse cellular events, and may be involved in regulating gene expression as a result of histone accessibility. 17 NAP1, which is the best characterized member of the NAP family, plays a role in the exchange process of histone H2A and H2B dimers from assembled nucleosomes in DNA replication as a histone chaperone, and NAP1 may assist nucleosome sliding.…”
mentioning
confidence: 99%